Switching imidazole reactivity by dynamic control of tautomer state in an allosteric foldamer - David P. Tilly; Jean-Paul Heeb; Simon J. Webb; Jonathan Clayden (Nature Communications, 2023)
Abstract Molecular biology achieves control over complex reaction networks by means of molecular systems that translate a chemical input (such as ligand binding) into an orthogonal chemical output (such as acylation or phosphorylation). We present an artificial molecular translation device that converts a chemical input – the presence of chloride ions – into an unrelated chemical output: modulation of the reactivity of an imidazole moiety, both as a Brønsted base and as a nucleophile. The modulation of reactivity operates through the allosteric remote control of imidazole tautomer states. The reversible coordination of chloride to a urea binding site triggers a cascade of conformational changes in a chain of ethylene-bridged hydrogen-bonded ureas, switching the chain’s global polarity, that in turn modulates the tautomeric equilibrium of a distal imidazole, and hence its reactivity. Switching reactivities of active sites by dynamically controlling their tautomer states is an untapped strategy for building functional molecular devices with allosteric enzyme-like properties.